1962
DOI: 10.1007/bf00033785
|View full text |Cite
|
Sign up to set email alerts
|

Sterility in the rice hybrids and its significance

Abstract: The degree of sterility resulting in F l hybrids has been used by several workers while considering the relative affinity between the different varieties and sub-species within a species and that between different species . The authors contend that sterility cannot be used as a criterion and present spikelet sterility data in F l hybrids of inter-varietal, inter-subspecific and interspecific crosses in the cultivated rices to support this contention . They conclude that the evolution of the three sub-species (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1972
1972
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Indeed, there is evidence that crossing IR70369A with the restorer IR73885-1-4-3-2-1R produced a relatively resistant variety, despite a general susceptibility of IR70369A-derived hybrids when other restorers were used ( Table S1 ). The availability of alternative A lines for three-line hybrid breeding has increased in recent decades [ 41 , 42 , 43 ], and, furthermore, two-line breeding systems based on inducing sterility through heat (i.e., thermosensitive genetic male sterile lines, TGMS) or photosensitivity (i.e., photosensitive genetic male sterile lines, PGMS) are now available [ 44 , 45 , 46 ], which can help avoid any susceptibilities that may be linked to specific female parents.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, there is evidence that crossing IR70369A with the restorer IR73885-1-4-3-2-1R produced a relatively resistant variety, despite a general susceptibility of IR70369A-derived hybrids when other restorers were used ( Table S1 ). The availability of alternative A lines for three-line hybrid breeding has increased in recent decades [ 41 , 42 , 43 ], and, furthermore, two-line breeding systems based on inducing sterility through heat (i.e., thermosensitive genetic male sterile lines, TGMS) or photosensitivity (i.e., photosensitive genetic male sterile lines, PGMS) are now available [ 44 , 45 , 46 ], which can help avoid any susceptibilities that may be linked to specific female parents.…”
Section: Discussionmentioning
confidence: 99%
“…The early work of Kato in 1928 based on morphological and serological characteristics (Richharia et al 1962 ) confirmed the empirical classification of rice varieties in China and identified two subspecies, Japonica (Geng) and Indica (Hsien) (Oka 1988 ). The distinction also involves F1 hybrid sterility and differentiated patterns of adaptation.…”
Section: Introductionmentioning
confidence: 94%
“…The resulting hybrids produce both fertile and infertile grains that are unsuitable for seed harvesting, thereby promoting the commercialization of hybrid varieties. Hybrid varieties have generally higher (up to 15%) yields than inbred rice varieties, and seed quality is generally better, thereby avoiding seed-borne diseases and reducing seed contamination with weeds [ 3 , 7 , 8 ]. However, hybrids—particularly early-generation hybrids—have often been associated with high damage from insect herbivores and diseases [ 1 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%